2022
DOI: 10.3390/ijms23084107
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Anti-HMGB1 Antibody Attenuates Neurodegeneration in an Experimental Animal Model of Glaucoma

Abstract: Neuroinflammation is a crucial process for the loss of retinal ganglion cells (RGC), a major characteristic of glaucoma. High expression of high-mobility group box protein 1 (HMGB1) plays a detrimental role in inflammatory processes and is elevated in the retinas of glaucoma patients. Therefore, this study aimed to investigate the effects of the intravitreal injection of an anti-HMGB1 monoclonal antibody (anti-HMGB1 Ab) in an experimental animal model of glaucoma. Two groups of Spraque Dawley rats received epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…EVO has been widely used as a method in studies of glaucoma rodents [ 11 , 23 ], leading to significant RGC loss to imitate neurodegeneration in glaucoma [ 20 , 24 ]. In a previous study of our own [ 8 ], we found that IOP elevation also impairs vascular endothelial function and autoregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVO has been widely used as a method in studies of glaucoma rodents [ 11 , 23 ], leading to significant RGC loss to imitate neurodegeneration in glaucoma [ 20 , 24 ]. In a previous study of our own [ 8 ], we found that IOP elevation also impairs vascular endothelial function and autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Optic nerve degeneration was assessed by p-phenylenediamine (PPD)-stained optic nerve cross sections, as previously described [ 19 , 20 ]. The semi-thin cross sections of optic nerves were taken from 1.0 mm posterior to the eyeballs.…”
Section: Methodsmentioning
confidence: 99%
“…Neuroinflammation is observed in human glaucomatous optic nerves and retinas, 54 and it is a common feature of animal models of the disease. 55 57 Aging, a major risk factor for glaucoma, leads to chronic low-grade inflammation of the CNS. 58 In Spp1 KO astrocytes, production of inflammatory mediators is chronically elevated, even at a young age, whereas the neurotrophic factors are down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, newest findings demonstrate the great potential of caffeine for RGC neuroprotection with its anti-inflammatory and anti-oxidative properties (4) illustrating new perspectives for the medical management of retinal diseases in the future. In accordance with that, our research group focuses the application of antibody-based immunotherapeutics as promising starting point for the treatment of glaucoma, which specifically target pathogenic key molecules in the retina such as HMGB1 (5) or α-synuclein (6) and provide ocular neuroprotection by different modes of action. Since the pharmaceutical trend nowadays is toward the development of small drug compounds with enhanced bioactivity (7), the downsizing of large biomolecules and the restriction to only biologically active binding sites has become of great interest for clinical manufacturing.…”
Section: Introductionmentioning
confidence: 89%